Biased Teachers and Gender Gap in Learning Outcomes: Evidence from India - Sonali Rakshit; Soham Sahoo (Institute of Labor Economics (IZA), 2021)
We investigate the effect of stereotypical beliefs of teachers on the learning outcomes of secondary school students in India. We measure teacher's bias through an index capturing teacher's subjective beliefs about the role of gender and other characteristics in academic performance. We tackle the potential endogeneity of teacher's subjective beliefs by controlling for teacher fixed effects in a value-added model that includes lagged test scores of students. We find that a standard deviation increase in the biased attitude of the math teacher increases the female disadvantage in math performance by 0.07 standard deviation over an academic year. The effect is stronger among medium-performing students and in classes where the majority of students are boys. The negative effect of biased teachers is statistically insignificant for female teachers who also reduce gender gap among medium-performing students. Mediation analysis shows that biased teachers negatively affect girls' attitude towards math as compared to boys.
Keywords: I24; J16; J24; 330; learning outcomes; value-added model; gender; teachers; stereotypes; India